Unbiased approach to identify and assess efficacy of human SARS-CoV-2 neutralizing antibodies - Xia Cao; Junki Maruyama; Heyue Zhou; Yanwen Fu; Lisa Kerwin; Colin Powers; Rachel A. Sattler; John T. Manning; Alok Singh; Reyna Lim; Laura D. Healy; Sachi Johnson; et al. (Scientific Reports, 2022)
Abstract Coronavirus disease 2019 (COVID-19) continues to significantly impact the global population, thus countermeasure platforms that enable rapid development of therapeutics against variants of SARS-CoV-2 are essential. We report use of a phage display human antibody library approach to rapidly identify neutralizing antibodies (nAbs) against SARS-CoV-2. We demonstrate the binding and neutralization capability of two nAbs, STI-2020 and STI-5041, against the SARS-CoV-2 WA-1 strain as well as the Alpha and Beta variants. STI-2020 and STI-5041 were protective when administered intravenously or intranasally in the golden (Syrian) hamster model of COVID-19 challenged with the WA-1 strain or Beta variant. The ability to administer nAbs intravenously and intranasally may have important therapeutic implications and Phase 1 healthy subjects clinical trials are ongoing.